Islamic State: Breeding a New Generation of Jihadists - Syed Huzaifah bin Othman Alkaff (2016)
The terrorist group ISIS is institutionalising an education system that will perpetuate its violent legacy by moulding the young in its fold with ideas of bigotry and hatred. The group has been belligerent about its intention to perpetrate violence and provoke conflict globally.